Evaluation of the Anti-Salivary IgG Response Specific to Anopheles Vectors of Malaria in Children under Five Seen in Health Care Settings in Areas of Low and High Insecticide Resistance in Southern Benin - Tokponnon, Tatchémè Filémon (My University, 2023)
The widespread use of long-lasting insecticidal nets (LLINs) is a major intervention method for malaria control. While coverage of LLINs has increased, there is a need for information on the operational effectiveness of nets deployed in the field in the context of malaria vector resistance to insecticides used for impregnation. The development of specific anti-malarial biomarkers to assess exposure to mosquito bites is an important development in evaluations. The aim of this study was to characterize the human IgG antibody response to Anopheles gSG6-P1 saliva, a salivary peptide antigen previously shown to be a relevant biomarker of human exposure to Anopheles bites, in order to assess the LLINs under field conditions in areas of low and high vector resistance to insecticides. We analyzed data from 240 randomly selected children (<5 years) of whom 70% were sleeping under LLINs in four (04) communes of Benin. No significant difference was observed in the expression of the anti-saliva IgG antibody in the different zones (high and low resistance zone) as well as in cases and controls (p > 0.05). Furthermore, the same finding was observed for antibody expression in children whether or not they used LLINs on the day before the survey (p = 0.7724). Similarly, gender and especially age, major factors of variation in the adaptive immune response, did not have a significant effect on IgG expression
Keywords: Case-Controls; LLINs; Malaria Morbidity; Pyrethroids Resistance; Antibodies; Bite Exposure; Biomarkers; Benin